EFFECTIVENESS FARMER CARD PROGRAM IN OKU REGENCY SOUTH SUMATRA PROVINCE - Mokhamad Fauzian; Fifian Permata Sari; Yetty Oktarina (Bajang Institute, 2022)
The government issued a national program policy of farmer cards aimed at minimizing problems in the procurement, distribution and supervision of subsidized fertilizers at the farmer level. The implementation of the national card program is considered not optimal at the farmer level, so that the implementation of this study aims to find out the level of effectiveness of the national farmer card program in Ogan Komering Ulu Regency, South Sumatra Province. Data analysis is carried out using Allocation to Collection Ratio (ACR) analysis with descriptive quantitative methods. The results of the Allocation to Collection Ratio (ACR) analysis based on the farmer card that has been printed show the effectiveness of the national farmer card program in Ogan Komering Ulu Regency of South Sumatra Province is at the Below Expection level.